Studies on utilization of the yeast strain I-7-43 - fusant between Saccharomyces cerevisiae and Saccharomyces diastaticus in agricultural distillery. - Małgorzata WOLSKA; Bogusław CZUPRYŃSKI; Grzegorz KŁOSOWSKI; Katarzyna KOTARSKA (Kvasný průmysl, 2004)
The aim of our study was to determine the usefulness (in full-production scale under common technical conditions of agricultural distillery) of the agricultural yeast strain I-7-43 obtained by electrofusion of protoplasts and characterized by both the fermentative activity and ability to hydrolysis of starch. The fermentations of rye mashes were carried out with application of standard and limited to 90 %, 80 % and 70 % doses of saccharifying preparation i.e. glucoamylase San-Super 240 L (Novo-Nordisk). The control fermentations were carried out with application of the standard agricultural distillery strain As-4. It was found that under distillery conditions, the yeast strain I-7-43 was characterized by the high fermentative activity and dynamics of ethanol production comparable with the values obtained in the case of the standard strain As-4. Independently of the glucoamylase dose applied, the ethanol yield from starch was appropriate i.e. 61,7-61, 8 dm3/100 kg; after I day of fermentation 70-80 % of total alcohol quantity was produced and after II days 95-97 %, respectively. Our studies show that thanks to amolilytic abilities of fusant I-7-43, 30% of dose of saccharifying preparation can be saved under full-production conditions without detriment to technological effects of the spirit production process. The contents of aldehydes, methanol and acids in raw rye spirits were lower than the values permissible by Polish Standard. The positive results of verification of the fermentative activity and amylolitic abilities of the yeast strain I-7-43 in full-production scale empower us to implement it into the distillery practice.The aim of our study was to determine the usefulness (in full-production scale under common technical conditions of agricultural distillery) of the agricultural yeast strain I-7-43 obtained by electrofusion of protoplasts and characterized by both the fermentative activity and ability to hydrolysis of starch. The fermentations of rye mashes were carried out with application of standard and limited to 90 %, 80 % and 70 % doses of saccharifying preparation i.e. glucoamylase San-Super 240 L (Novo-Nordisk). The control fermentations were carried out with application of the standard agricultural distillery strain As-4. It was found that under distillery conditions, the yeast strain I-7-43 was characterized by the high fermentative activity and dynamics of ethanol production comparable with the values obtained in the case of the standard strain As-4. Independently of the glucoamylase dose applied, the ethanol yield from starch was appropriate i.e. 61,7-61, 8 dm3/100 kg; after I day of fermentation 70-80 % of total alcohol quantity was produced and after II days 95-97 %, respectively. Our studies show that thanks to amolilytic abilities of fusant I-7-43, 30% of dose of saccharifying preparation can be saved under full-production conditions without detriment to technological effects of the spirit production process. The contents of aldehydes, methanol and acids in raw rye spirits were lower than the values permissible by Polish Standard. The positive results of verification of the fermentative activity and amylolitic abilities of the yeast strain I-7-43 in full-production scale empower us to implement it into the distillery practice.